2016
DOI: 10.12659/msm.897149
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Diffusion-Weighted Imaging (DWI) Apparent Diffusion Coefficient (ADC) in Patients with Hyperacute Cerebral Infarction Receiving rt-PA Intravenous Thrombolytic Therapy

Abstract: BackgroundThe aim of this study was to investigate the potential value of apparent diffusion coefficient (ADC) of diffusion-weighted imaging (DWI) in the prognosis of patients with hyperacute cerebral infarction (HCI) receiving intravenous thrombolytic therapy with recombinant tissue plasminogen activator (rt-PA).Material/MethodsFrom June 2012 to June 2015, 58 cases of HCI (<6 h) undergoing rt-PA intravenous thrombolytic therapy (thrombolysis group) and 70 cases of HCI (<6 h) undergoing conventional antiplatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…NIHSS was used to evaluate neurological function prior to intravenous tPA and at 24 hours and 7 days post-treatment 14. Modified Rankin scale (mRS) and Barthel Index (BI) was used to evaluate functional outcome at 90 days 14. An improvement of NIHSS score of 8 or a score of 0–1 on NIHSS score was considered good neurological recovery.…”
Section: Methodsmentioning
confidence: 99%
“…NIHSS was used to evaluate neurological function prior to intravenous tPA and at 24 hours and 7 days post-treatment 14. Modified Rankin scale (mRS) and Barthel Index (BI) was used to evaluate functional outcome at 90 days 14. An improvement of NIHSS score of 8 or a score of 0–1 on NIHSS score was considered good neurological recovery.…”
Section: Methodsmentioning
confidence: 99%
“…According to Sui et al., and Drake-Pérez et al. [11 , 12] , these types of findings are inconsistent with acute or subacute infarctions. White et al.…”
Section: Discussionmentioning
confidence: 97%
“…These findings are also similar to those of previous studies [ 33 ]. Sui, H. J found that the ADC value of the cerebral infarction lesion area will gradually change from low to high with time [ 34 ], and in the subacute phase (days 2–10), as the acid-base balance of the perfusion area continues to alkalinize, the APTw reduction area shrinks, and the perfusion area improves correspondingly with the opening of the lateral branch circulation and reconstruction, and “false normalization” can occur. The average course of infarction cases in this group was 115 h and 50 min (about 4.8 days), from 49 h and 30 min to 238 h and 47 min (about 2–10 days), in the stage of acidosis to alkalinization change, resulting in microenvironments that affect APT values, such as PH concentration, which do not appear to change significantly.…”
Section: Discussionmentioning
confidence: 99%